2008
DOI: 10.1111/j.1525-1314.2008.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

P–T–t–D paths of Everest Series schist, Nepal

Abstract: U(-Th)-Pb geochronology, geothermobarometric estimates and macro-and micro-structural analysis, quantify the pressure-temperature-time-deformation (P-T-t-D) history of Everest Series schist and calcsilicate preserved in the highest structural levels of the Everest region. Pristine staurolite schist from the Everest Series contains garnet with prograde compositional zoning and yields a P-T estimate of 649 ± 21°C, 6.2 ± 0.7 kbar. Other samples of the Everest Series contain garnet with prograde zoning and staurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 58 publications
(242 reference statements)
2
86
1
1
Order By: Relevance
“…In order to place the results of this study into the regional tectonic context, this section provides a brief background to the geological structure as well as the style and timing of metamorphism and melting within the GHS. Detailed descriptions of various aspects of the GHS are given by Pognante and Benna (1993), Carosi et al (1999b), Searle et al (2003Searle et al ( , 2006, Law et al (2004) and Jessup et al (2006Jessup et al ( , 2008a. Structural mapping of isograds, quartz fabrics, and thermobarometric data across the Everest transect fit all the requirements for the midcrustal channel-flow model.…”
Section: Geology Of the Mount Everest Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to place the results of this study into the regional tectonic context, this section provides a brief background to the geological structure as well as the style and timing of metamorphism and melting within the GHS. Detailed descriptions of various aspects of the GHS are given by Pognante and Benna (1993), Carosi et al (1999b), Searle et al (2003Searle et al ( , 2006, Law et al (2004) and Jessup et al (2006Jessup et al ( , 2008a. Structural mapping of isograds, quartz fabrics, and thermobarometric data across the Everest transect fit all the requirements for the midcrustal channel-flow model.…”
Section: Geology Of the Mount Everest Regionmentioning
confidence: 99%
“…A-A cross section is modified from Searle et al (2003). pressure gradient between the Tibetan Plateau and the indenting Indian plate (Beaumont et al 2001Jamieson et al 2004;Godin et al 2006). The Everest region of Nepal and South Tibet provides one of the best three-dimensional exposures of the top of the GHS slab, with deeply incised glacial valleys of Rongbuk (north of Everest) and Kangshung (east of Everest) carving windows into the exhumed midcrustal channel (Carosi et al 1998(Carosi et al , 1999aSearle 2003;Searle et al 2003Searle et al , 2006Jessup et al 2006Jessup et al , 2008aCottle et al 2007). The northernmost extension of the GHS extends to the Ama Drime massif (Jessup et al 2008b;Cottle et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic and trace element modeling shows that the Himalayan leucogranites formed by the incongruent melting of muscovite during decompression (Harris et al, 1995;Harris and Inger, 1992;Harris and Massey, 1994). U-Pb dating of metamorphic monazites and igneous minerals within leucogranites showed that the Himalayan melts formed over the period c. 24-11 Ma, with the majority intruded during the period 21-19 Ma (e.g., Cottle et al, 2009;Godin et al, 2001Godin et al, , 2006Searle et al, 1997aSearle et al, , 1999, The channel flow model based on regional mapping combined with strain analyses, thermobarometry, and U-Pb geochronology of Greater Himalayan rocks along the Everest transect, Nepal, and South Tibet, after Searle et al (2003Searle et al ( , 2006, Law et al (2006Law et al ( , 2011, and Jessup et al (2006Jessup et al ( , 2008. Insets show alignment of inverted metamorphic isograds in the MCT zone along the base and right-way-up isograds along the STD low-angle normal fault along the top of the extruding midcrustal layer.…”
Section: Miocene Channel Flow Along the Himalayamentioning
confidence: 99%
“…The Higher Himalayan Crystallines (HHC), representing the deeply buried and then exhumed Indian continent, provide an excellent natural laboratory for studying the continental collisional orogenesis because all observations of Himalayan age can be attributed to a single, known orogenic process-the ongoing collision of India with Asia (Rubatto et al, 2013). Despite the significance of the metamorphism and partial melting of the HHC for understanding the formation and evolution of the Himalayan orogen, the following issues still remain highly controversial: (1) the peak-metamorphism of the HHC was estimated at different P-T conditions, such as upper amphibolite-facies to granulite-facies (e.g., Kohn, 2008;Rubatto et al, 2013;Searle et al, 2006;Yakymchuk and Godin, 2012), high-pressure (HP) granulite-facies (Chakungal et al, 2010;Ding et al, 2001;Guilmette et al, 2011;Liu and Zhong, 1997), or eclogite-facies (Corrie et al, 2010;Groppo et al, 2007;Kali et al, 2010); (2) the peakmetamorphism of the HHC was dated at different times, such as 26-20 Ma (Corrie et al, 2010;Jessup et al, 2008;Su et al, 2012;Xu et al, 2010), or 40-30 Ma (Ding et al, 2001;Liu et al, 2007a,b;Zhang et al, 2010Zhang et al, , 2012; (3) various mechanisms were assigned for partial melting of the HHC, such as fluid-saturated anatexis (Harris et al, 1993;Patino Douce and Harris, 1998), prograde melting during continental subduction (Groppo et al, 2010;Guilmette et al, 2011;Visona and Lombardo, 2002), decompression melting under fluid-absent conditions (Harris and Massey, 1994;Harrison et al, 1997;H.F. Zhang et al, 2004;J.…”
Section: Introductionmentioning
confidence: 99%